Analysis Of Co-Creation Strategy For Digital Entertainment Products Of PT Telekomunikasi Indonesia For The B2B2X Segment - Febriantoro, Seto; Tricahyono, Dodie (Publisher Cv. Inara, 2024)
Research analyzes PT Telekomunikasi Indonesia’s response to the decline in traditional communication services (landlines, mobile phones, SMS) due to consumer shifts toward free communication platforms like WhatsApp, Telegram, and Line. Additionally, the rise of entertainment content platforms (music, video, gaming) has driven changes in the telecommunications industry. In response, PT Telekomunikasi Indonesia’s B2B2X segment aims to gain a competitive advantage by collaborating with various stakeholders to create mutually beneficial business value. The research utilized methods including observations, supporting documents, and interviews, structured with the Co-Creation Design Framework. The findings show that the Co-Creation strategy successfully established collaborative value in PT Telekomunikasi Indonesia’s digital entertainment products for the B2B2X segment.